2005
DOI: 10.1161/circulationaha.104.498758
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Calcium Dynamics and Anisotropic Reentry in Isolated Canine Pulmonary Veins and Left Atrium

Abstract: Background-Rapid activations due to either focal discharge or reentry are often present during atrial fibrillation (AF) in the pulmonary veins (PVs). The mechanisms of these rapid activations are unclear. Methods and Results-We studied 7 isolated, Langendorff-perfused canine left atrial (LA) and PV preparations and used 2 cameras to map membrane potential alone (Vm, nϭ3) or Vm and intracellular calcium simultaneously (Ca i , nϭ4). Rapid atrial pacing induced 26 episodes of focal discharge from the proximal PVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
3
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 25 publications
7
112
3
1
Order By: Relevance
“…6 These manipulations did not cause significant APD shortening to induce late phase 3 early afterdepolarizations. Rather, they facilitate the development of delayed afterdepolarizations.…”
Section: Ca I Dynamics and Cholinergic Af In Heart Failurementioning
confidence: 89%
See 3 more Smart Citations
“…6 These manipulations did not cause significant APD shortening to induce late phase 3 early afterdepolarizations. Rather, they facilitate the development of delayed afterdepolarizations.…”
Section: Ca I Dynamics and Cholinergic Af In Heart Failurementioning
confidence: 89%
“…The overall incidence of focal discharge was calculated by the average of the total number of focal discharges in 4 seconds. APD 80 was the interval between phase 0 and the time of 80% repolarization, measured at a pacing cycle length of 500 ms. Monoexponential fit was used to compute the time constant of the decline of Ca i transient (τ) at a pacing cycle length of 1,000 ms. APD 80 and τ values in four nonpaced PV-LA preparations from normal dogs used in a previously published study 6 were measured for control. Fast Fourier transform was used to determine the frequency at each pixel during 4 seconds of AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patterson et al (2006) found that the continuous increase in relaxing period tension was an important cause of EAD, in which the increasing intracellular calcium concentration of the relaxing period was the cause of inducing AF. By using an optical mapping technique, Chou et al (2005) detected that when dogs' atrial muscle cell membrane and pulmonary vein regeneration or nerve automatic activity decreased, the rate of forming cardiac intracellular calcium overload and EAD decreased significantly, which would promote the recovery of AF.…”
Section: Discussionmentioning
confidence: 99%